Partial 16S ribosomal RNA gene from thermophilic Bacillus sp. and Geobacillus sp. strains isolated from East Coast Hot spring - Tengku Abdul Hamid, Tengku Haziyamin; Hasan, N. (2020)
This is a collection of partial 16S ribosomal RNA gene from thermophilic Bacillus sp. and Geobacillus sp. strains isolated from East Coast Hot spring. Strain Bacillus sp. LH1, LH2, LH3, LH4 and LH1 were isolated fro La hot spring in Hulu Terengganu and Geobacillus sp. S1B4 and B1B1 were isolated from Sg. lembing and Bentong Hot spring, Pahang.